2001
DOI: 10.1021/jm0101996
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of a Prodrug of Doxorubicin Designed to Provide Reduced Systemic Toxicity and Greater Target Efficacy

Abstract: Doxorubicin (Dox) can provide some stabilization in prostate cancer; however, its use is limited because of systemic toxicities, primarily cardiotoxicity and immunosuppression. The administration of a prodrug of doxorubicin, designed to permit selective activation by the tumor, would reduce general systemic exposure to the active drug and would thereby increase the therapeutic index. Prostate specific antigen (PSA) is a serine protease with chymotrypsin-like activity that is a member of the kallikrein gene fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 15 publications
2
69
0
Order By: Relevance
“…A series of oligopeptide cytotoxic drug conjugates containing Gln-Ser have shown PSA-targeted pro-drug activities. 8 Thus, similar peptide sequences were prepared for the fluorogenic PSA FAST agents in which both the C and N termini were attached to a lysine molecule modified at the ε-amino group by an NIR fluorophore. The NIR-modified peptides were nonfluorescent due to the proximity of the two fluorophores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of oligopeptide cytotoxic drug conjugates containing Gln-Ser have shown PSA-targeted pro-drug activities. 8 Thus, similar peptide sequences were prepared for the fluorogenic PSA FAST agents in which both the C and N termini were attached to a lysine molecule modified at the ε-amino group by an NIR fluorophore. The NIR-modified peptides were nonfluorescent due to the proximity of the two fluorophores.…”
Section: Discussionmentioning
confidence: 99%
“…A nine amino acid oligopeptide substrate based on a known PSAcleavable tetrapeptide sequence, Chg-Gln-Ser-Ser, 8 was purchased as the trifluoroacetic acid salt from Tufts Core Facility, Boston, MA. VivoTag-S 750 was obtained from PerkinElmer, Inc. (Waltham, MA).…”
Section: Synthesis and Characterization Of Fluorogenic Psa Fast Agentsmentioning
confidence: 99%
“…Garsky et al [41] reported that DOX had a limited utility in prostate cancer due to systemic toxicities, primarily cardiotoxicity and myelosuppresion. The administration of a prodrug of DOX designed to permit selective activation by the tumor, would reduce general systemic exposure to the DOX.…”
Section: Macromolecular Prodrugs Of Doxorubicinmentioning
confidence: 99%
“…Glutaryl-Hyp-Ala-Ser-Chg-Gln-SerLeu-DOX (Fig. 10), as the peptide-DOX conjugate was described as 20-fold selective against human prostate [41]. A peptide prodrug of DOX (Leu-Dox) transformed into DOX in tumor cells by cathepsin-like enzymes and exhibited superior antitumor activity than DOX.…”
Section: Macromolecular Prodrugs Of Doxorubicinmentioning
confidence: 99%
“…Several approaches have been developed in order to deliver specifically Doxorubicin to tumor cells using monoclonal antibodies (mAbs) or small peptides as carrier molecules (Arap et al, 1998;Nagy et al, 1998;King et al, 1999;Stan et al, 1999;Garsky et al, 2001;Langer et al, 2001). Targeted chemotherapy couples a drug to a carrier molecule (ligand), and depends on the ability of the ligand to bind selectively to the target tumor cells in such a way that it may increase the drug concentration near the tumor while decreasing systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%